Proposta curricular por complexos de estudo das Escolas Itinerantes do Paraná e Base Nacional Comum Curricular (BNCC): uma análise sobre diferentes currículos para a formação escolar - Ferreira, Roberto Gonçalves (2022)
The research developed an analysis of two curricular proposals, with the main objective of understanding how the proposals of the Study Complexes of Itinerant Schools of Paraná and the National Common Curricular Base (BNCC) differ as a curriculum for school education. More specifically, it analyzes the elements that represent the centrality of the curriculum in the current curriculum policy of the National Common Curricular Base (BNCC), based on the changes in the Brazilian educational scenario. Therefore, based on these elements, we sought to contextualize the scenario on which the creation of the BNCC begins, in order to later understand the structure of this proposal. As a guide to better discuss the questions raised, the following question was started, in which it is understood as essential for carrying out the analyzes proposed here: How and why the curricular proposal of the Study Complexes and BNCC differ as a curriculum for school training? Therefore, the work seeks to bring important reflections in relation to the curriculum, from the analysis of the curriculum specificities of the BNCC, as a representative of that hegemonic conception of education, and that of the curriculum proposal by Study Complexes, as an autonomous and emancipating proposal of Itinerant Schools. and also to strengthen Rural Education. The research work was carried out from the collection of data through documental and bibliographic research. The documents used as a data source were: the document referring to the official curriculum proposal BNCC (2018) of the final years of Elementary School for the Brazilian educational system and the document Study Plan (2013), which presents the curriculum proposal by Study Complexes, final years of Elementary School, for the MST Itinerant Schools in Paraná. The analyzes concluded that the curricular conceptions and the social and educational contexts have moved and move, both the BNCC construction curriculum policy and the autonomous proposal of the Study Complexes. Thus, he considered the BNCC representative of an education linked to the hegemonic educational thought based on an ideal of teaching quality that does not correspond to the real training needs of rural subjects, such as the children of workers in general.